2021
DOI: 10.1021/acs.jcim.1c00527
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Influence of Osmolytes on Water Hydrogen-Bond Network: From Local Structure to Graph Theory Analysis

Abstract: Water structure in aqueous osmolyte solutions, deduced from the slight alteration in the water−water radial distribution function, the decrease in water−water hydrogen bonding, and tetrahedral ordering based only on the orientation of nearest water molecules derived from the molecular dynamics simulations, appears to have been perturbed. A careful analysis, however, reveals that the hydrogen bonding and the tetrahedral ordering around a water molecule in binary solutions remain intact as in neat water when the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 85 publications
0
21
0
Order By: Relevance
“…We observe that water–water hydrogen bonding is strengthened significantly in the hydration shell of the TMAO oxygen and moderately in the hydration shell of the methyl groups. In this respect, TMAO can be thought of as behaving like an anchor point within the water network, providing a site that can form strong hydrogen bonds from which the rest of the network can build and become more stable, as has been previously observed for other aqueous osmolytes 75 . Finally, we use the calculated values for hydrogen bond interaction energies between water molecules to determine the ratio at which the destabilising effect of external pressure is balanced by the stabilising effect of TMAO addition.…”
Section: Introductionmentioning
confidence: 80%
“…We observe that water–water hydrogen bonding is strengthened significantly in the hydration shell of the TMAO oxygen and moderately in the hydration shell of the methyl groups. In this respect, TMAO can be thought of as behaving like an anchor point within the water network, providing a site that can form strong hydrogen bonds from which the rest of the network can build and become more stable, as has been previously observed for other aqueous osmolytes 75 . Finally, we use the calculated values for hydrogen bond interaction energies between water molecules to determine the ratio at which the destabilising effect of external pressure is balanced by the stabilising effect of TMAO addition.…”
Section: Introductionmentioning
confidence: 80%
“…It is noted that DMSO indeed exhibited superior performance in antifreezing, showing greater α b (39.15%) and AF mass (1.17 g UF g CPA –1 ) values than the other cryoprotectants ( p < 0.05). Among the NADESs, Pro:Sor (1:1) was believed to show more desired thermal behavior for cryopreservation because more systematic water was found to stay unfrozen, which could be due to the stronger hydration of sorbitol than that of glucose, making Pro:Sor (1:1) bind more water molecules and prevent them from nucleation. To further shed light upon how could the hydrogen-bonding strengths of NADESs change when decreasing temperature, the LF-NMR T 2 inversion spectra (Figure B) of 25% ( w / w ) NADESs at different temperatures were obtained, showing greater T 2 values at 298 K (580.53–766.34 ms), but significantly shortened ones at 263 K (peak 1: 10.09–11.95 ms; peak 2: 82.06–102.96 ms), which could suggest that the systems were not the homogenous ones but indeed showed significantly reinforced hydrogen-bonding interactions when decreasing temperature. , Besides, the T 2 signal intensities of NADESs at 263 K were found to be enhanced by different degrees as shown in subfigures of Figure B, probably indicating the formation of denser hydrogen-bonding networks, which could help to restrain the water molecular motion more effectively .…”
Section: Resultsmentioning
confidence: 99%
“…It is noted that DMSO indeed exhibited superior performance in antifreezing, showing greater α b (39.15%) and AF mass (1.17 ) values than the other cryoprotectants (p < 0.05). Among the NADESs, Pro:Sor (1:1) was believed to show more desired thermal behavior for cryopreservation because more systematic water was found to stay unfrozen, which could be due to the stronger hydration of sorbitol than that of glucose, 63 making Pro:Sor (1:1) bind more water molecules and prevent them from nucleation. To further shed light upon how could the hydrogen-bonding strengths of NADESs change when , which could suggest that the systems were not the homogenous ones but indeed showed significantly reinforced hydrogen-bonding interactions when decreasing temperature.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In another molecular dynamics study on aqueous solutions of various osmolytes, including ethanol, glycerol, glucose, trehalose, and sorbitol, it was found that all of the studied osmolytes were well integrated into the hydrogen-bonded water network [38]. Furthermore, these compounds behaved as "hubs" in the network, with their degree of hydrogen bonding affecting the connectivity and other properties of the network.…”
Section: Correlation Of Water Activity Datamentioning
confidence: 98%